The complete mitochondrial genomes of Pangasius nasutus and P. conchophilus (Siluriformes: Pangasiidae) - Siti Amalia, Aisyah Abdul Halim; Yuzine, Esa; Gan, Han Ming *; Amir Asyraf, Zainudin; Siti Azizah, Mohd Nor (Taylor and Francis Group, 2023)
The catfish, Pangasius nasutus and P. conchophilus, are often misidentified between each other due to their similar morphology. Thus, the current study was conducted to differentiate them based on a molecular approach. The complete mitochondrial genomes of P. nasutus and P. conchophilus obtained from the Pahang River (Peninsular Malaysia) were sequenced, assembled, and annotated using next-generation sequencing (NGS). A 16,465 bp and 16,470 bp length mitogenome sequence of P. nasutus and P. conchophilus, respectively, was generated, each containing 13 protein genes, 22 tRNAs, and two rRNAs, typical of most vertebrates. This is the first report of the complete mitochondrial genome sequences of P. nasutus and P. conchophilus. These data are a valuable genetic resource for future studies of these two commercially important species.